Student Entrepreneurship Training through Product Sales in the Politeknik Mardira Indonesia Campus Environment - Muhammad Fikry Januar; Zulfikar Fauzi; Imma Ismaniar; Mochammad Anjar Albagja (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
This community service program is carried out with the aim of developing entrepreneurial spirit and potential among Politeknik Mardira Indonesia  students through training activities and practice selling goods in the campus area. In this activity, students are given the subject matter of entrepreneurship, marketing principles, micro business financial management, and practical operational strategies. The implementation of the next process includes educational sessions, interactive training, sales simulations, and student business performance assessments. Based on the results of the evaluation, this activity succeeded in increasing students' understanding of the business world and training their skills in managing small-scale businesses. Furthermore, this program also fosters creativity, initiative, and confidence of students in starting a business independently. This activity is expected to be a sustainable means in producing a generation of young entrepreneurs from the university environment.